2020
DOI: 10.1111/bcpt.13457
|View full text |Cite|
|
Sign up to set email alerts
|

Involvement of H2S, NO and BDNF‐TrkB signalling pathway in the protective effects of simvastatin against pentylenetetrazole‐induced kindling and cognitive impairments in mice

Abstract: Cognitive impairments are frequently observed in epileptic patients, particularly in memory function. 1 Pentylenetetrazole (PTZ) kindling is generally accepted as a chronic experimental animal model of epilepsy. PTZ kindling causes modifications in the molecular and cellular levels, which are responsible for the oxidative stress and neurodegenerative changes in hippocampus 2 and lead to memory dysfunction. 3 Reactive aldehydes, including malondialdehyde (MDA) and 4-hydroxynonena (4-HNE), are the product of lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In our model, atorvastatin did not modulate the expression of the synaptic proteins, PSD-95 and synaptophysin. Several hypotheses can be used to explain its pro-cognitive effects:-(i) the BDNF/trkB pathway might regulate the synaptic interactions affecting cognition and memory (Ahmed & Kamel, 2020); (ii) the increase in glucose uptake in the hippocampus might restore synaptic transmission (Lee et al, 2016) and (iii) the favourable cortical microenvironment and the preservation of the cortico-hippocampal network, as outlined above, might be neuroprotective (Cimino et al, 2007). The pro-cognitive effects of atorvastatin appeared to be unrelated to the expression of estrogen receptors, as the latter was not modulated by atorvastatin in males.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our model, atorvastatin did not modulate the expression of the synaptic proteins, PSD-95 and synaptophysin. Several hypotheses can be used to explain its pro-cognitive effects:-(i) the BDNF/trkB pathway might regulate the synaptic interactions affecting cognition and memory (Ahmed & Kamel, 2020); (ii) the increase in glucose uptake in the hippocampus might restore synaptic transmission (Lee et al, 2016) and (iii) the favourable cortical microenvironment and the preservation of the cortico-hippocampal network, as outlined above, might be neuroprotective (Cimino et al, 2007). The pro-cognitive effects of atorvastatin appeared to be unrelated to the expression of estrogen receptors, as the latter was not modulated by atorvastatin in males.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, atorvastatin activated the BDNF-trkB pathway at the lesion site. BDNF exhibits neuroprotective effects by binding to its specific receptor trkB but can also regulate synaptic interactions that may affect cognition and memory (Ahmed & Kamel, 2020). According to Fracassi et al (2019), the increase of BDNF induced by statins might be mediated by their action on the mevalonate pathway and/or on independent mechanisms relying on the nuclear receptors peroxisome proliferator-activated receptors alpha (PPARα/NR1C1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies demonstrated that a variety of cholesterol-independent pleiotropic effects of statins could be mediated through NO/cGMP pathway (27). Accordingly, Moezi et al (20) showed that NO signalling could mediate the anticonvulsant effect of atorvastatin probably through iNOS.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major barriers to clearly defining the role of H2S in the brain has been the prior inability to precisely measure H2S concentrations in isolated tissues [34]. While prior reports have indirectly assessed the role of H2S on cognitive function in rodents with chemically-kindled seizures [35], no study has yet quantified the progressive changes in H2S levels in the brains during the kindling process itself. Further, little work has been conducted to establish how acute seizures influence H2S levels in the brain and periphery (i.e.…”
Section: Introductionmentioning
confidence: 99%